Crystalline forms for sodium reduction

The preparation of sodium salt crystals with specific forms by anti-solvent crystallization method solves the problem of decreasing salt feeling when reducing the sodium content of food in the prior art, and achieves the effect of providing the same salt feeling under low sodium conditions, and is simple in process and easy to apply.

JP7657256B2Active Publication Date: 2025-04-04FRITO LAY NORTH AMERICA INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023084689
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2017-10-27
Filing Date
2023-05-23
Publication Date
2025-04-04
Estimated Expiration
2038-10-26

AI Technical Summary

Technical Problem

In the prior art, when reducing the sodium content in food, it is difficult to maintain or improve the salt feeling of the food, and commonly used methods have problems such as taste changes, cost increases and complexity.

Method used

Sodium salt crystals with specific morphology, such as sodium salt crystals in the snail form, are prepared by anti-solvent crystallization, which have a larger surface area and faster solubility, thereby providing the same salt feeling at low sodium content.

Benefits of technology

It realizes that while maintaining or improving the salt feeling of food, reducing the sodium content in food, avoiding the problems of taste changes and cost increase, and the process is simple and easy to be used in industrial use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007657256000007
    Figure 0007657256000007
  • Figure 0007657256000008
    Figure 0007657256000008
  • Figure 0007657256000009
    Figure 0007657256000009
Patent Text Reader

Abstract

To provide a salt composition for reducing a sodium content; and to provide a production method corresponding thereto.SOLUTION: A salt composition includes multiple salt crystals having an edge length of 10 μm-150 μm, a surface area of 0.19-0.23 m2 / g, and a hall density of less than 0.8 g / cm3, and further the multiple salt crystals include here a first part having a mature hopper cube morphology, a second part having a simple hopper cube morphology, a third part having a halo cube morphology, and a fourth part having a solid cube morphology.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Novel aspects of the present disclosure relate to salt compositions and corresponding methods of manufacture, as well as the resulting food products formed with the salt compositions. More particularly, the present disclosure is directed to novel salt compositions having unique shapes that enhance their perceived saltiness. [Background technology]

[0002] Although salt is a popular and effective seasoning, in recent years, some consumers have expressed a preference for foods with lower levels of sodium. To address these changing preferences, snack food manufacturers have adapted a number of different methods to reduce sodium content. In one simple method, snack food recipes have been modified to use less salt. However, such changes often result in undesirable taste profiles. As a result, flavor rebalancing may be utilized in conjunction with sodium salt reduction, where other flavors attempt to mask the reduced saltiness. Sodium contrast is another method of sodium reduction that relies on the consumption of two differently salted portions to increase the perceived saltiness when compared to the consumption of a uniformly salted food portion. However, these currently used methods suffer from various drawbacks, including but not limited to undesirable changes in taste, increased cost, and / or complexity. Thus, there remains a need in the art to reduce the sodium content of savory foods without reducing the perceived saltiness or otherwise reducing the consumer's perception of the product. Summary of the Invention

[0003] A novel aspect of the present invention is directed to salt products and corresponding methods of manufacture for reducing sodium content. In one embodiment, the sodium content is at least 0.19 to 0.23 m 2 / g and a surface area of ​​0.8 g / cm3 Disclosed is a salt composition formed from a plurality of salt crystals having a Hall density of less than 1000 nm. In some embodiments, at least a portion of the salt composition is in a hopper cube form.

[0004] In another embodiment, a method for producing a salt crystallization product is disclosed, the method including: providing an antisolvent solution; adding a salt solution to the antisolvent solution to form a supersaturated solution, wherein the salt solution has a concentration of solute greater than 15% by weight, and the mass ratio of the salt solution to the antisolvent solution is 1:20 to 1:1.25; and crystallizing the supersaturated solution to form a crystallization product of at least 0.19 to 0.23 m. 2 / g and a surface area of ​​0.8 g / cm 3 The method includes forming a salt composition comprising a plurality of salt crystals having a Hall density of less than 100 nm.

[0005] In yet another embodiment, a food product is disclosed that includes an exterior surface and a salt composition applied to the exterior surface, the salt composition having a thickness of at least 0.19 to 0.23 μm. 2 / g and a surface area of ​​0.8 g / cm 3 The present invention relates to a method for producing a salt crystal having a Hall density of less than 100 nm.

[0006] Other aspects, embodiments, and features of the present invention will become apparent from the following detailed description when considered in conjunction with the accompanying drawings, in which each identical or substantially similar component shown in the various figures is designated by a single numeral or symbol. For purposes of clarity, not every component is labeled in every figure. Also, not every component of each embodiment of the present invention is shown unless illustration is necessary for one of ordinary skill in the art to understand the invention. [Brief description of the drawings]

[0007] The novel features believed characteristic of this invention are set forth in the appended claims, however the invention itself and its preferred mode of use, together with objects and advantages thereof, will best be understood by reference to the following detailed description of illustrative embodiments when read in conjunction with the accompanying drawings.

[0008] [Figure 1] FIG. 1 illustrates a salt crystal having a hopper cube morphology according to an exemplary embodiment.

[0009] [Figure 2A] FIG. 2A is a photomicrograph showing a representative crystal morphology formed by antisolvent crystallization according to an exemplary embodiment. [Figure 2B] FIG. 2B is a photomicrograph showing a representative crystal morphology formed by antisolvent crystallization according to an exemplary embodiment. [Figure 2C] FIG. 2C is a micrograph showing a representative crystal morphology formed by antisolvent crystallization according to an example embodiment. [Figure 2D] FIG. 2D is a micrograph showing a representative crystal morphology formed by antisolvent crystallization according to an example embodiment. [Figure 2E] FIG. 2E is a photomicrograph showing representative crystal morphologies formed by antisolvent crystallization according to an illustrative embodiment.

[0010] [Figure 3A] FIG. 3A is a micrograph showing a representative sample of salt crystals formed from salt solutions with varying salt concentrations. [Figure 3B] FIG. 3B is a micrograph showing a representative sample of salt crystals formed from salt solutions with varying salt concentrations.

[0011] [Figure 4A] FIG. 4A is a photomicrograph showing a representative sample of salt crystals formed from antisolvent at varying ethanol concentrations. [Figure 4B]FIG. 4B is a micrograph showing a representative sample of salt crystals formed from antisolvent at varying ethanol concentrations.

[0012] [Figure 5A] FIG. 5A is a photomicrograph showing a representative sample of salt crystals formed from a supersaturated solution exposed to varying stirring speeds. [Figure 5B] FIG. 5B is a photomicrograph showing a representative sample of salt crystals formed from a supersaturated solution exposed to varying stirring speeds.

[0013] [Figure 6A] FIG. 6A is a photomicrograph showing a representative sample of salt crystals formed in the presence of a salt solution additive. [Figure 6B] FIG. 6B is a photomicrograph showing a representative sample of salt crystals formed in the presence of a salt solution additive. [Figure 6C] FIG. 6C is a photomicrograph showing a representative sample of salt crystals formed in the presence of a salt solution additive. [Figure 6D] FIG. 6D is a photomicrograph showing a representative sample of salt crystals formed in the presence of a salt solution additive. [Figure 6E] FIG. 6E is a photomicrograph showing a representative sample of salt crystals formed in the presence of a salt solution additive. [Figure 6F] FIG. 6F is a photomicrograph showing a representative sample of salt crystals formed in the presence of a salt solution additive.

[0014] [Figure 7] FIG. 7 is a flow chart for forming a salt composition according to an example embodiment.

[0015] [Figure 8] FIG. 8 is a graph showing the dissolution behavior of hopper cubes as a function of particle size. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Salt is an important ingredient in food, especially in savory snacks such as potato chips, pretzels, and tortilla chips. Due to its size and shape, typical salt only partially dissolves in the mouth during consumption so that most of the salt is swallowed without contributing to the perceived saltiness of the food. Thus, at least one previous attempt to reduce sodium content has involved finely granulating salt crystals to increase the dissolution rate of the applied salt in the mouth, which results in an increased perception of saltiness. However, widespread use of finely granulated salt is limited by the ability to apply salt using readily available equipment. Smaller salt particles do not flow easily, and as a result, micronized salt particles cannot be applied using commonly available equipment. Salt applied in seasoning savory snacks may adhere to the food with a layer of oil, and it is believed that very small salt crystals that are completely exposed within the layer of oil do not contribute much to the perceived saltiness.

[0017] Thus, novel aspects of the exemplary embodiments disclosed herein recognize the need to create a salt product with an enhanced perceived saltiness, which can be applied to foods at lower concentrations to achieve a similar level of saltiness, but which can be applied using conventionally available equipment. In particular, the present disclosure relates to salt compositions and associated methods of manufacture that create salt products having salt crystals with a particular morphology that increases their dissolution rate such that the applied salt can be perceived as saltier than conventionally available salt crystals.

[0018] The morphology of salt crystals can be modified using antisolvent crystallization, a method of forming salt crystals by mixing a salt solution with an antisolvent. An antisolvent is a solution that reduces the solubility of the solute in the salt solution. When combined with a salt solution, the resulting mixture forms a supersaturated solution with a driving force of supersaturation that causes crystallization. The driving force of supersaturation is the difference in chemical potential between the molecules in the solution and the molecules in the bulk of the crystalline phase. In a non-limiting example, when ethanol is the antisolvent and aqueous sodium chloride is the salt solution, antisolvent crystallization proceeds according to the following equation:

[0019] NaCl(aqueous solution) + EtOH → EtOH(aq) + NaCl(precipitation)

[0020] The morphology of salt crystals from antisolvent crystallization is highly process specific. Thus, the size and shape of salt crystals formed by antisolvent crystallization are influenced by many different variables, including the concentration of salt in the salt solution, the alcohol content in the antisolvent solution, the presence of additives, and the mixing conditions. The mixing condition variables can be further broken down into mixing temperature and agitation speed. The influence of each of these variables is then believed to determine the corresponding effect on the morphology of the salt crystals and ultimately the perceived saltiness. As discussed in more detail below, the selection of certain variables results in the creation of salt crystals with a hopper cube morphology that provides an enhanced dissolution rate compared to other conventionally available salt crystals.

[0021] FIG. 1 is a diagram of a salt crystal having a hopper cube morphology according to an exemplary embodiment. As used herein, a salt crystal having a hopper cube morphology may alternatively be referred to as a hopper cube. The hopper cube 100 can be described as a cube-shaped crystal having six faces, each of which has four edges 104 that generally form a square. Each face 102 has a series of square steps 106 that recede inwardly to each face 102. When compared to a traditional salt crystal having the same outer dimensions, the hopper cube 100 has a larger surface area but a lower density than the traditional salt crystal. As a result, the hopper cube 100 has a faster dissolution rate than a traditional salt crystal having the same dimensions.

[0022] Hopper cubes are formed when crystals grow faster at the edges of the crystal faces than in the center. The rate of crystal growth is determined by the supersaturation driving force - high supersaturation leading to rapid nucleation and dendritic growth (i.e. faster edge growth). The solute concentration and supersaturation driving force are highest when the salt solution and antisolvent are mixed first resulting in the formation of crystals with more elaborate morphologies such as hopper cubes. As the solute concentration decreases and the force of supersaturation decreases, the rate of crystal growth slows allowing the faces of the crystal to fill in. Thus, crystals formed from antisolvent crystallization have a range of sizes and morphologies as can be seen in more detail in Figure 2.

[0023] Since the salt content in a salt solution contributes to the supersaturation driving force of a supersaturated solution, the salt content was varied to determine the corresponding effect on the morphology of salt crystals. Specifically, salt solutions with various concentrations were prepared with sodium chloride dissolved in water according to the following equation:

[0024] Salt concentration = {weight of salt (g) / weight of salt solution (g)} x 100

[0025] Using the above equation, 15 wt%, 20 wt% and 25 wt% salt solutions were prepared and each was mixed with an antisolvent solution of 95% ethanol by volume to form salt crystals. The resulting crystal morphology was analyzed. The 15 wt% salt solution was not saturated enough to produce salt crystals. As can be seen in Figure 2, both the 20 wt% and 25 wt% salt solutions produced hopper cubes, but the 25 wt% salt solution produced salt crystals with a wider size range and formed complex hopper cubes.

[0026] For cube-shaped crystals, size was determined by measuring along the edge of the salt crystal from one corner to the adjacent corner. If the salt crystal lacked clearly defined edges, as in complex hopper cubes, size was measured between two adjacent corners of an imaginary cube that was sized to encircle the entire perimeter of the cube-shaped crystal.

[0027] 2a-2e are micrographs showing representative crystal morphologies formed by antisolvent crystallization according to exemplary embodiments, shown for added complexity. FIG. 2a shows a representative solid cube having a size of about 20 μm, but varying between 10-30 μm. The surface of the solid cube may have a pattern of irregular morphology. FIG. 2b shows a representative halo cube having a size of less than 50 μm, but more specifically having a size in the range of 30-50 μm. Halo cubes generally have flat faces (i.e., lacking a square step) with a hole in the center of one or more faces. FIG. 2c shows a representative simple hopper cube formed by antisolvent crystallization. The hopper cube has six faces, each of which has four straight edges, and one or more square steps receding inwardly to each face. Additionally, the simple hopper cube has a size of less than 100 μm, but more specifically having a size in the range of 50-100 μm. FIG. 2d shows a representative mature hopper cube. The mature hopper cube has six faces, each with four straight edges, and multiple square steps receding inward on each face. Additionally, the mature hopper cube has a size greater than 100 μm, but more specifically has a size in the range between 100-150 μm. FIG. 2e shows a representative complex hopper cube formed by antisolvent crystallization. Complex hopper cubes are generally cubic crystals with a size smaller than 150 μm, more specifically in the range between 80-150 μm. Complex hopper cubes differ from simple hopper cubes and mature complex hopper cubes in that complex hopper cubes lack defined continuous edges extending from corner to corner. Instead, complex hopper cubes are generally cubic crystals with one or more edges that have at least two directions of growth. For example, the complex hopper cube of FIG. 2e has an edge 104 with one direction of growth along line 108a and another direction of growth along line 108b.

[0028] When a 25 wt% salt solution is mixed with an antisolvent formed from 95 vol% ethanol in the absence of mixing or elevated temperature, the higher driving force of supersaturation results in the formation of complex hopper cubes as shown in Figure 2e as well as hopper cubes ranging in crystal morphology as shown in Figures 2a-2d. When a 20 wt% salt solution is mixed with an antisolvent in the absence of mixing or elevated temperature, the relatively low driving force of supersaturation is insufficient to create hopper cubes but forms crystals with morphologies ranging from the mature hopper cubes of Figure 2d to the solid cubes of Figure 2a.

[0029] For example, Figures 3a and 3b are micrographs showing representative samples of salt crystals formed from salt solutions with varying salt concentrations: Figure 3a shows salt crystals formed from a salt solution containing 20% ​​salt by weight, and Figure 3b shows salt crystals formed from a salt solution containing 25% salt by weight.

[0030] Thus, in an exemplary embodiment, a salt solution of more than 15% by weight of solute can be added to an antisolvent to create hopper crystals by antisolvent crystallization, while in another embodiment, a salt solution of more than 15% by weight but less than 27% by weight of solute achieves salt crystals having a hopper cube morphology.

[0031] Given that the salt content of the salt solution adversely affected salt crystal morphology, with a 25 wt% salt solution giving hopper cubes, the alcohol content of the antisolvent solution was varied to determine the corresponding effect on crystal morphology. In a non-limiting embodiment, the antisolvent solution contained ethanol, the amount of which was varied as shown below. When 15 g of a 25 wt% salt solution was mixed with 150 g of 100% ethanol by volume (i.e., 200 proof ethanol), the salt rapidly nucleated at the interface between the antisolvent and the salt solution, resulting in the formation of numerous small salt crystal nuclei having a size of about 5 μm. These fine particles aggregated into a cake after drying and were no longer easily separated into individual particles. However, when the same salt solution was poured into 150 g of 95% ethanol by volume, salt crystals were obtained that included hopper cubes ranging in size from 30 to 150 μm along with some solid cubes of about 20 μm. The results of this experiment are shown in FIG. 4.

[0032] Figures 4a and 4b are photomicrographs showing representative samples of salt crystals formed by antisolvent crystallization at varying ethanol concentrations. In particular, Figure 4a shows salt crystals formed from a mixture of 15 g of 25 wt% salt solution with 150 g of 100 vol% ethanol, and Figure 4b shows 15 g of 25 wt% salt solution mixed with 150 g of 95 vol% ethanol in water. As previously discussed, salt crystals formed from 100 vol% ethanol gave small crystal nuclei, whereas salt crystals formed from 95 vol% ethanol gave a range of crystal morphologies ranging from hopper cubes to solid cubes.

[0033] Thus, in a non-limiting embodiment, the antisolvent crystallization method uses an antisolvent that is less than 100% ethanol by volume (i.e., less than 200 proof ethanol). In another embodiment, the antisolvent solution has a range of more than 80% but less than 100% ethanol by volume in water, and in a more specific embodiment, the antisolvent is a solution that is 95% ethanol by volume in water.

[0034] The salt crystals having a hopper cube shape were obtained by mixing the salt solution and the antisolvent as described above in a mass ratio of the salt solution to the antisolvent in the range of 1:20 to 1:1.25, more specifically in the range of 1:10 to 3:5.

[0035] The variables of mixing conditions can be further decomposed into mixing temperature and stirring speed. Although mixing temperature affects solubility and reaction rate, the temperature was maintained near room temperature, 20-30°C, more specifically near 25°C (298K), so that the method for producing salt crystals having hopper cube morphology does not require the use of heat exchangers, which increases the complexity and cost of production. Therefore, while the mixing temperature was maintained at room temperature, the stirring speed was varied to determine the corresponding effect on the crystal morphology.

[0036] To test the effect of mixing speed on salt crystal morphology, 30 g of a 25 wt% salt solution was mixed with 100 g of an antisolvent made from 95 vol% ethanol while stirring. Stirring was performed using a conventional magnetic stir bar. In the first test, the salt solution was mixed with the antisolvent and stirred at 125 RPM. In the second test, the salt solution was mixed with the antisolvent and stirred at 1100 RPM. The results are shown in Figure 5.

[0037] Figures 5a and 5b are photomicrographs showing representative samples of salt crystals formed from supersaturated solutions exposed to varying stirring speeds. Figure 5a shows salt crystals formed by stirring at 125 RPM, and Figure 5b shows salt crystals formed by stirring at 1100 RPM. Compared to salt crystals formed by antisolvent crystallization methods lacking mixing, the stirred samples yielded smaller cubes, but with a large number of complex hopper cubes. High stirring speeds likely increase the probability of contact between solute molecules, allowing for more rapid crystal growth associated with the formation of complex hopper cubes. Hopper cube sizes ranged from 40 to 120 μm. Smaller crystal sizes were observed at the highest stirring speeds, which may be attributed to at least some breakage during stirring.

[0038] Thus, in one embodiment, an antisolvent crystallization method is disclosed that includes mixing a supersaturated solution formed from the antisolvent and salt solution with the salt solution using a magnetic stir bar rotating at less than 1100 RPM. In another embodiment, the magnetic stir bar rotates at 125 RPM or less to obtain larger crystals. In a final embodiment, the salt solution is mixed with the salt solution without mixing to obtain the largest possible salt crystals.

[0039] Additives can also be introduced into the salt solution prior to combining with the antisolvent. Additives alter the morphology of the salt crystals by acting as capping agents that alter the surface free energy of the crystal faces through adsorption and / or chemical interactions. The following additives were examined to determine their effect on crystal morphology: potassium chloride (KCl), sodium alginate (Na(C6H8O6)n), citric acid (C6H8O7), tricalcium phosphate (Ca3(PO4)2), barbituric acid (C4H4N2O3), glycine (C2H5NO2), sodium citrate (HOC(COONa)(CH2COONa)2) and calcium lactate (C6H 10 Of these, barbituric acid, glycine and sodium citrate have been shown to change the morphology of salt crystals at 0.5% by weight of the salt mass in the salt solution, the results of which are shown in Figure 6.

[0040] Figures 6a-6f are photomicrographs showing representative samples of salt crystals formed in the presence of salt solution additives. Modified salt solutions were formed by mixing one of the additives at 0.5% by weight into 30 g of 25% by weight salt solution. The modified salt solution was then combined with 100 g of 95% by volume ethanol at room temperature in the presence of gentle stirring. Figures 6a and 6b show crystals that formed when barbituric acid was mixed into the salt solution before combining with the antisolvent. Salt crystals also include solid cubes, halo cubes, simple hopper cubes, complex hopper cubes, and horned cubes. Horned cubes are crystals that have eight horn-like structures, each of which extends from the center of the crystal structure to a different corner of an imaginary cube drawn around the periphery of the crystal structure. Horned cubes form when the driving force of supersaturation is at its highest, which is evident by the complexity of the dendrite formation. As the solute is consumed and the supersaturating power decreases, complex hopper cubes, mature hopper cubes, simple hopper cubes, halo cubes and solid cubes are formed in their place, respectively.

[0041] Figures 6c and 6d show the crystals formed when glycine was added to the salt solution before combining with the antisolvent. The resulting crystals can generally be described as a mass of smaller cubes forming strands or clumps of similar solid cubes. The smaller cubes include solid cubes, halo cubes, and simple hopper cubes.

[0042] Figures 6e and 6f show the crystals formed when sodium citrate was added to the salt solution before combining with the antisolvent. The resulting crystals may generally be described as rounded versions of the crystals formed in the absence of sodium citrate. Thus, the cubes may be described as similar solid cubes, halo cubes, simple hopper cubes, and complex hopper cubes, but with rounded edges and curved concave surfaces instead of square steps.

[0043] 7 is a flow chart of a method of forming a salt composition consistent with an exemplary embodiment. In a first step, an anti-solvent solution is provided (step 702). In a non-limiting embodiment, the anti-solvent solution is ethanol that is less than 200 proof (less than 100% ethanol by volume), and in another embodiment, the ethanol is 180-200 proof (90-100% ethanol by volume). At least one exemplary embodiment uses an anti-solvent solution that is 190 proof (95% ethanol by volume).

[0044] In a second step, a salt solution is provided (step 704). The salt solution is formed from a solute dissolved in a solvent, which is combined at room temperature and mixed until all solute particles are completely dissolved. The room temperature can be in the range of 293-303 K (20-30° C.). In one embodiment, the solute is present in an amount greater than 15% by weight of the salt solution. In another embodiment, the solute is 15-27% by weight of the salt solution. In an exemplary embodiment disclosed, the solute includes sodium chloride and the solvent is water.

[0045] In some embodiments, the solute may include other additives in an amount of 0.3-0.8% by weight of the sodium chloride. An exemplary embodiment includes one or more additives in an amount of about 0.5% by weight of the sodium chloride.

[0046] The salt solution is added to the antisolvent solution to form a supersaturated solution (step 706). The salt solution may be added to the antisolvent solution at room temperature in a weight ratio of 1:20 to 1:1.25. In this step, mixing of the salt solution and the antisolvent solution may be accomplished without stirring. In another embodiment, the addition of the salt solution to the antisolvent solution may be performed in the presence of stirring. The stirring may be performed by a magnetic stir bar rotating at less than 1100 RPM, and in some embodiments, the magnetic stir bar rotates at 125 RPM or less.

[0047] The supersaturated solution is crystallized to form a salt composition (step 708). In one embodiment, the supersaturated solution crystallizes for a period of 5-15 minutes, and in some specific embodiments, the supersaturated solution crystallizes for approximately 10 minutes. The salt composition includes hopper cube salt crystals. Optionally, the salt composition may be subjected to a post-processing step, which may include drying the salt composition using conventional methods, including, but not limited to, vacuum filtration and separation into one or more size-based fractions. Additionally, the process steps described above may be performed at room temperature, e.g., 20° C.-30° C., to eliminate the additional costs and complications associated with the use of heating elements.

[0048] The salt composition formed from antisolvent crystallization can be applied to a food product to achieve a desired level of saltiness. Alternatively, the salt composition may be separated into two or more fractions based on size, such that the salt composition added to the food product may contain salt crystals from a particular size range or a combination of two or more size ranges. The food product may be a salty snack, such as a potato chip, pretzel, or tortilla chip, having a relatively low moisture content, typically less than 5% by weight. The low moisture content limits the dissolution of the salt crystals in the salt composition and preserves the morphology of the salt crystals with a high dissolution rate. In a non-limiting embodiment, the salt composition is applied to an exterior surface of a food product to form a salty food product. The morphology of the salt crystals described herein enhances the dissolution rate, so that the salty food product requires less salt to achieve the same saltiness than commonly available salt. The comparative examples discussed below are evidence supporting the high dissolution rate of the novel salt compositions described herein.

[0049] Comparative Example

[0050] Salt crystals were formed by antisolvent crystallization and compared to commonly available salts. The antisolvent crystallization method used to form the salt compositions in Table 1 included mixing and not mixing a 25 wt% salt solution with a 95 vol% ethanol salt solution at room temperature. The resulting supersaturated solution was allowed to crystallize for approximately 10 minutes, and the resulting salt composition was filtered and dried for 12 hours at 120° C. and pressures above 25 inches of mercury. The salt compositions formed from antisolvent crystallization were characterized using the following conventional Designer Salt Testing protocols: Hall density (ASTM Standard B 212-99), bulk density (ASTM Standard B527-06) and flowability (ASTM standard B213-03, Method 1), and surface area (Brunauer-Emmett-Teller method using an ASAP 2020 automated surface area apparatus). These results were compared with commonly available salts: "15-micron salt", Alburger Select salt, Alburger Fine Flake salt, and pure salt. Table 1 lists the results of this testing.

[0051] [Table 1]

[0052] The salt crystals with hopper cube morphology had the lowest bulk density of all salts, but the second highest surface area, trailing only the 15-micron salt. The highest surface area of ​​the 15-micron salt is due to a portion of the crystals with small cube morphology. However, the small cubes of the 15-micron salt crystals negatively affect the flowability of the salt composition. The larger surface area contributes to a high dissolution rate.

[0053] The dissolution rates of Hopper Cube salt crystals were measured and compared to the dissolution rates of 15-micron salt, Alburger Select salt, Alburger Fine Flake and pure salt. Dissolution is the process by which a solid substance, such as a crystal, becomes a solute in a solution, such as water. The dissolution rate depends on many factors including temperature, agitation speed and surface area of ​​the particles. Smaller particles dissolve more quickly than larger particles. Thus, dissolution rates were determined for salt particles separated into the following particle size ranges: 45-90 μm, 90-150 μm, 150-212 μm, 212-250 μm and 250-300 μm.

[0054] Dissolution rates were determined by measuring the electrical conductivity of various salt compositions dissolved in artificial saliva based on the theory that dissolution of salt changes the ionic conductivity of the solution, which can be measured to quantify the rate of dissolution. Electrical conductivity is the ability of a solution to conduct electric current, which is attributed to the presence of dissolved solids that are ionized in polar solutions, such as water. Conductivity can be measured by applying an alternating current to two electrodes immersed in the solution and measuring the resulting voltage. The conductivity experiments described herein were performed at room temperature using a Thermo Scientific™ Orion™ Star A222 Conductivity Portable Meter.

[0055] The composition of the artificial saliva solution was mixed according to Table 2.

[0056] [Table 2]

[0057] The salt particles were oven dried at 120°C for 2 hours, then cooled to room temperature and kept in a desiccator before conducting conductivity tests. Three trials were performed for each salt particle size range. For each trial, 40 mg of salt was dissolved in 80 g of artificial saliva at room temperature while stirring with a magnetic stir bar rotating at 900 RPM. The results are shown in Tables 3-6.

[0058] Tables 3-6 compare the dissolution rates of commonly available salts listed in Table 1 with the novel antisolvent salt compositions described herein. More specifically, Tables 3-7 compare the time required to dissolve a 50% salt sample (t50%), an 80% salt sample (t80%), a 90% salt sample (t90%), and a 100% salt sample (t100%).

[0059] [Table 3]

[0060] [Table 4]

[0061] [Table 5]

[0062] [Table 6]

[0063] The data contained in Tables 3-6 show that t50%, t80%, t90% and t100% increase with increasing particle size. Additionally, different morphologies affect dissolution times. The 15-micron salt and antisolvent salt compositions dissolve more quickly than the pure salt, Alberger Select and Alberger Fine Flake Salt.

[0064] FIG. 8 is a graph showing the dissolution behavior of salt crystals formed by antisolvent crystallization as a function of particle size. The graph shows that smaller salt crystals generally dissolve more quickly than larger salt crystals. The y-axis is the electrical conductivity (c t ) and the initial conductivity (c0), normalized to 1 using the following formula:

[0065] y max =(ct -c0)×1 / ((c max -c0)) (In the formula, c max is the maximum conductivity reached)

[0066] Given that the novel salt composition formed by antisolvent crystallization has a higher dissolution rate than most commonly available salts, a comparison was made between a sample of commonly available potato chips (control sample) and samples salted with various concentrations of the novel salt composition (experimental sample). A panel of experts was asked to compare the control sample and the experimental sample along a number of attributes, one of which included saltiness. The panel concluded that the experimental sample, which had approximately 20% less sodium than the control sample, tasted similarly salty to the control sample.

[0067] The salt compositions, corresponding methods of manufacture, and reduced salt foods described herein are a significant improvement over the prior art because they allow for at least a 20% reduction in the amount of salt added to foods without a meaningful difference in the consumer's perception of saltiness. Additionally, a novel aspect of certain embodiments described herein is that sodium reduction can be achieved without the inclusion of compounds other than sodium chloride. Further embodiments

[0068] In further support of the disclosed invention, the following embodiments are provided:

[0069] In a first embodiment, the novel aspect of the present disclosure is a method for producing a gyro having a thickness of at least 0.19 to 0.23 m. 2 / g and a surface area of ​​0.8 g / cm 3 The present invention is directed to a salt composition comprising a plurality of salt crystals having a Hall density of less than 100 nm.

[0070] In another aspect of the first embodiment, the salt composition has a pH of at least 0.19 to 0.23 m 2 / g and a surface area of ​​0.8 g / cm 3and a plurality of salt crystals having a Hall density of less than about 100 nm, the salt composition further comprising one or more limitations selected from the following:

[0071] Here, the salt crystals are 0.90 g / cm 3 Further comprising a bulk density of less than;

[0072] wherein each of the plurality of salt crystals is at least 10 μm in size;

[0073] wherein the plurality of salt crystals comprises a first portion having a mature hopper cube morphology;

[0074] wherein the first portion of the salt crystals are between 80 and 150 μm in size;

[0075] wherein the plurality of salt crystals further comprises a second portion having a simple hopper cube morphology, a third portion having a halo cube morphology, and a fourth portion having a solid cube morphology;

[0076] wherein the second portion of the plurality of salt crystals has a size of 50-100 μm, the third portion of the plurality of salt crystals has a size of 30-50 μm, and the fourth portion of the plurality of salt crystals has a size of 15-25 μm;

[0077] wherein the plurality of salt crystals further comprises a fifth portion having a complex hopper cube morphology;

[0078] wherein the fifth portion of the salt crystals are 80 to 150 μm in size;

[0079] wherein the plurality of salt crystals comprises sodium chloride;

[0080] wherein the plurality of salt crystals further comprises an additive in an amount of 0.3 to 0.8% by weight of the salt crystals; and

[0081] Here, the additive is selected from the group consisting of barbituric acid, glycine and sodium citrate.

[0082] In a second embodiment, a novel aspect of the disclosure is directed to a method of forming a salt composition, the method including: providing an antisolvent solution; adding a salt solution to the antisolvent solution to form a supersaturated solution, wherein the salt solution has a concentration of greater than 15 wt. % solute, wherein the mass ratio of the salt solution to the antisolvent solution is in the range of 1:20 to 1:1.25; and crystallizing the supersaturated solution to form a salt composition having a concentration of at least 0.19 to 0.23 m. 2 / g and a surface area of ​​0.8 g / cm 3 The salt composition comprises a plurality of salt crystals having a Hall density of less than 1000 nm.

[0083] In another aspect of the second embodiment, a novel aspect of the disclosure is directed to a method of forming a salt composition, the method including: providing an antisolvent solution; adding a salt solution to the antisolvent solution to form a supersaturated solution, wherein the salt solution has a concentration of greater than 15 wt. % solute, wherein a mass ratio of the salt solution to the antisolvent solution is in the range of 1:20 to 1:1.25; and crystallizing the supersaturated solution to form a salt composition having a concentration of at least 0.19 to 0.23 m. 2 / g and a surface area of ​​0.8 g / cm 3 and forming a salt composition having a plurality of salt crystals having a Hall Density of less than 100 nm, the method further comprising one or more limitations selected from the following:

[0084] wherein the salt solution comprises a solute dissolved in a solvent, wherein the salt solution is less than 27% by weight salt solution;

[0085] where the solute comprises sodium chloride and the solvent comprises water;

[0086] where the antisolvent is ethanol;

[0087] wherein the antisolvent is less than 100% by volume of ethanol;

[0088] wherein the antisolvent is greater than 90% by volume ethanol;

[0089] Here, the supersaturated solution crystallizes for 5 to 15 minutes to form a salt composition;

[0090] wherein the supersaturated solution crystallizes for about 10 minutes to form a salt composition;

[0091] wherein the mixing step further comprises mixing the supersaturated solution with a magnetic stir bar rotating at no more than 125 RPM;

[0092] wherein the method further comprises drying the salt composition;

[0093] wherein the drying step further comprises vacuum filtration;

[0094] Here, the salt solution contains an additive in the range of 0.3 to 0.8% by weight relative to the solute;

[0095] wherein the additive is selected from the group consisting of barbituric acid, glycine and sodium citrate;

[0096] wherein the salt composition comprises a hopper cube having a size in the range of 80 to 150 μm;

[0097] Here, the hopper cube is 0.23 to 0.19 m 2 / g surface area;

[0098] wherein the salt composition further includes simple hopper cubes, halo cubes and solid cubes;

[0099] wherein the salt composition further comprises a complex hopper cube;

[0100] wherein the process steps are carried out at a temperature of 20-30° C.; and

[0101] Here, the method further comprises filtering the salt composition to obtain a select particle size.

[0102] In a third embodiment, a novel aspect of the disclosure is directed to a food product comprising an exterior surface; and a salt composition for application to the exterior surface of the food product, wherein the salt composition has a salt content of at least 0.19 to 0.23 μg / g. 2 / g and a surface area of ​​0.8 g / cm 3 The present invention comprises a plurality of salt crystals having a Hall density of less than 100 nm.

[0103] In another aspect of the third embodiment, a novel aspect of the disclosure is directed to a food product comprising an exterior surface; and a salt composition for application to the exterior surface of the food product, wherein the salt composition has a salt content of at least 0.19 to 0.23 μg / g. 2 / g and a surface area of ​​0.8 g / cm 3 and wherein the food product further comprises one or more limitations selected from the following:

[0104] wherein each of the plurality of salt crystals is at least 10 μm in size;

[0105] wherein the salt composition comprises a first portion having a mature hopper cube morphology;

[0106] wherein the first portion of the salt crystals are between 80 and 150 μm in size;

[0107] wherein the plurality of salt crystals further comprises a second portion having a simple hopper cube morphology, a third portion having a halo cube morphology, and a fourth portion having a solid cube morphology;

[0108] wherein the second portion of the plurality of salt crystals has a size of 50-100 μm, the third portion of the plurality of salt crystals has a size of 30-50 μm, and the fourth portion of the plurality of salt crystals has a size of 15-25 μm;

[0109] wherein the plurality of salt crystals further comprises a fifth portion having a complex hopper cube morphology;

[0110] wherein the fifth portion of the salt crystals are 80-150 μm in size; and

[0111] Here, the plurality of salt crystals includes sodium chloride.

[0112] Although the embodiments of the present invention have been described with reference to certain elements, any elements described in the embodiments described herein are exemplary and may be omitted, substituted, added, combined, or rearranged as applicable to form new embodiments. A person skilled in the art will recognize upon reading this specification that such further aspects disclosed herein are effectively disclosed herein. For example, the disclosure may incorporate the features, structure, size, shape, arrangement, or composition of an element, or a process for making or using an element or combination of elements, the features, structure, size, shape, arrangement, or composition of an element, or a process for making or using an element or combination of elements described herein, with other elements or combinations of elements to provide further embodiments.

[0113] Further, when a description is made of an element or group of elements, further embodiments can consist essentially of or consist of the element or group of elements. Also, although the open-ended term "comprising" is generally used herein, further embodiments can be formed by substituting "consisting essentially of" or "consisting of."

[0114] While the present invention has been particularly shown and described with reference to preferred embodiments, those skilled in the art will recognize that various changes in form and detail may be made therein without departing from the spirit and scope of the invention. The inventor intends that those skilled in the art may employ such modifications as appropriate to implement the invention other than as the inventor has specifically set forth herein. Accordingly, this invention includes all modifications and equivalents of the subject matter recited in the claims appended hereto as permitted by applicable law. Also, any combination of the above-described elements in all possible variations thereof is encompassed by the invention unless otherwise indicated herein or otherwise clearly contradicted by context.

Claims

1. Edge length from 10μm to 150μm, 0.19 to 0.23 m 2 / g BET surface area and 0.8 g / cm 3 1. A salt composition comprising a plurality of salt crystals having a Hall density of less than 1000 nm, wherein the plurality of salt crystals comprises a first portion having a mature hopper cube morphology, a second portion having a simple hopper cube morphology, a third portion having a halo cube morphology, and a fourth portion having a solid cube morphology.

2. Multiple salt crystals at 0.90 g / cm 3 10. The salt composition of claim 1, further comprising a bulk density of less than 1000 nm.

3. 2. The salt composition of claim 1, wherein the second portion of the plurality of salt crystals is 50-100 μm in size, the third portion of the plurality of salt crystals is 30-50 μm in size, and the fourth portion of the plurality of salt crystals is 15-25 μm in size.

4. 10. The salt composition of claim 1, further comprising a fifth portion, wherein the plurality of salt crystals has a complex hopper cube morphology.

5. 5. The salt composition of claim 4, wherein the plurality of salt crystals in the fifth portion are 80 to 150 μm in size.

6. 10. The salt composition of claim 1, wherein the plurality of salt crystals comprises sodium chloride.

Citation Information

Patent Citations

  • Crystal precipitation method utilizing liquid-liquid interface and novel crystal

    JP2006281193A

  • Manufacturing method of sodium chloride crystal

    JP2006282476A

  • Anti-solvent solidification process

    JP2006524565A